Map interactive guide using palm Kuala Lumpur (MIGuP-KL) / Noor Azly Mohamed - Noor Azly, Mohamed (2003)
There are many web sites provide information about map for certain places in Malaysia. However, from the study I have done, there is no significant number shown that any of the website provide service on Palm. This study has been the idea to develop a website or more accurately a web clipping solution for Map Interactive using Palm-Kuala Lumpur (MlGuP). Before developing MIGuP, several subject keywords related to the project have been covered. Among the subject keywords are map, interactive and Palm device. Discussion with my supervisor Cik Rafidah Mohd Nor ha been carried out to under rand the current requirement and desired system to be developed. MIGuP contain two main modules that are User Module and Administrator Module. User Module will displays information to client or user. The Administrator Module maintain the MIGuP system to make sure the service are available at any time. MIGuP will be developed based on the client/server architecture, which included web server, database server and development workstation. Personal Web Server (PWS) will be used on the Microsoft Windows 98 platform with connection to the Microsoft Acess 2000. At the end of the project, MIGuP is expected to be an online interactive web-base system to obtain and distribute information dynamically within the usage of Palm device. The successful of MIGuP will widen the usage of the Palm OS device and at the same time encourage the tourism industry in Malaysia.